2018
DOI: 10.1177/1934578x1801300221
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufacini from the Skin of Bufo bufo gargarizans Induces Apoptosis, Possibly via Activation of the Wnt/β-Catenin Pathway, in Human Osteosarcoma Cells

Abstract: Cinobufacini (huachansu) is a traditional Chinese medicine extracted from the skin of Bufo bufo gargarizans, which is used in clinical cancer therapy. The purpose of this study was to investigate the signaling pathways regulating cinobufacini-induced apoptosis in the osteosarcoma cell line, U 2 OS. We used 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay to evaluate the effects of cinobufacini on cell proliferation in U 2 OS cells. Changes in cell morphology and apoptosis were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This study showed that AB23A in combination with bufalin increased β-catenin protein, while decreased GSK-3β in LC cell strains (SMMC-7721 and MHCC97), suggesting the ability of AB23A and bufalin to activate the Wnt/β-catenin axis. The results were similar to the previous studies that AB23A activates the Wnt/β-catenin axis in human osteosarcoma cells by downregulating GSK-3β and upregulating β-catenin [20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study showed that AB23A in combination with bufalin increased β-catenin protein, while decreased GSK-3β in LC cell strains (SMMC-7721 and MHCC97), suggesting the ability of AB23A and bufalin to activate the Wnt/β-catenin axis. The results were similar to the previous studies that AB23A activates the Wnt/β-catenin axis in human osteosarcoma cells by downregulating GSK-3β and upregulating β-catenin [20].…”
Section: Discussionsupporting
confidence: 92%
“…Abnormal activation of the Wnt/β-catenin axis has a close connection with the development of many human tumors like prostate can-cer [43,44]. Ma et al reported that AB23A induced human osteosarcoma cell apoptosis through Wnt/β-catenin signal activation [20]. However, the impacts of AB23A+bufalin on the Wnt/β-catenin axis in LC cells have not been studied so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cinobufacini injection (CI), extracted from the skin of the Bufo bufo gargarizans Cantor, has the effects on clearing away heat and toxic material, inducing diuresis for removing edema. CI has been broadly used for clinical cancer treatment [9], including OS [10,11], but the pharmacological mechanisms governing these processes remains unknown, which limits its clinical application and promotion.…”
Section: Introductionmentioning
confidence: 99%